2019
DOI: 10.1002/jcp.29155
|View full text |Cite
|
Sign up to set email alerts
|

Rce1 suppresses invasion and metastasis of hepatocellular carcinoma via epithelial‐mesenchymal transition induced by the TGF‐β1/H‐Ras signaling pathway

Abstract: Ras converting enzyme 1 (Rce1) plays an important role in invasion and metastasis of malignancy. However, the mechanism has not yet been fully explored in hepatocellular carcinoma (HCC). Primarily, we investigated the expression of Rce1 and H-Ras influence on patient prognosis through the clinical data. Further, we analyzed the regulatory effects of Rce1/H-Ras signal pathway on the epithelial-mesenchymal transition (EMT) in vitro and in vivo. Finally, we screened out the protein which bonds with Rce1 by CO-IP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Oppositely, several studies have also reported its suppressive functions in HCC, which hinges on the intracellular p53 status (37,38). HRAS, a member of the RAS gene family that is closely related to multiple human cancers, and studies have shown that it engages in mediating EMT of HCC cells through the TGF-β1/HRAS axis, thereby promoting tumor invasion and metastasis (39). And the expression of GNA14 is decreased in tumor tissues and is related to the poor OS of patients with HCC, indicating that it can be a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Oppositely, several studies have also reported its suppressive functions in HCC, which hinges on the intracellular p53 status (37,38). HRAS, a member of the RAS gene family that is closely related to multiple human cancers, and studies have shown that it engages in mediating EMT of HCC cells through the TGF-β1/HRAS axis, thereby promoting tumor invasion and metastasis (39). And the expression of GNA14 is decreased in tumor tissues and is related to the poor OS of patients with HCC, indicating that it can be a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PIK3R1 in HCC tissues was higher than that in adjacent normal tissues, and knockdown of PIK3R1 could suppress the proliferation and migration of HCC cells [ 51 ]. Besides, HRAS gene was associated with the early invasion and metastasis of HCC caused by epithelial-mesenchymal transition [ 52 ]. Therefore, previous studies made our results more plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that EMT is the driving force for cancer cells metastasis, the EMT is an important mechanism in the early stage of cancer metastasis, to study the molecular mechanism of EMT is the key to improve tumor diagnosis and treatment. [26,27] The decreased expression of E-cadherin and Vimentin, N-cadherin and other proteins have increased which have been considered to be the most signi cant feature of EMT. The changes of these EMT markers have enabled cancer cells to obtain features that promote migration and invasion.…”
Section: Discussionmentioning
confidence: 99%